Sleep disorders and dental caries related to salivary alpha-amylase among dental students - Abrar A Ahmed; Ban S Diab; Samaneh Razeghi (College of Dentistry/ University of Baghdad, 2024)
College students experience several sleep problems, which may impact academic performance and health including dental health. The purpose of the study was to assess the effect of sleep disorders on dental caries status related to salivary alpha-amylase among dental students. Methods: A cross-sectional comparative study was done among dental students, aged 22 to 23 years attending the College of Dentistry, Al- Kufa University, 270 students have participated in this study. A questionnaire completed by those students was used to collect information about sleep disorders using Pittsburg sleep quality index. According to Manji et al (1989) criteria, teeth affected by dental caries were recorded. Unstimulated salivary samples were chemically analyzed for the detection of alpha-amylase using Enzyme Linked Immuno-Sorbent Assay. Results: It was found that the prevalence of poor sleep quality among dental students was 58.9% while the prevalence of dental caries in students with good sleep quality (75.68%) was higher than that for students with poor sleep quality (71.07%), also founded decay,missing and filling surfaces and decay level three of caries severity were significantly higher for students who had a good sleep quality. The mean value of salivary alpha-amylase was higher for students who had poor sleep quality yet difference was not significant. Conclusion: Caries experience was significantly higher among students with good sleep quality that was not affected by salivary amylase.